What drives business cycles and international trade in emerging market economies? - Marcelo Sánchez (European Central Bank (ECB), 2007)
This paper investigates the role of domestic and external factors in explaining business cycle and international trade developments in fifteen emerging market economies. Results from signrestricted VARs show that developments in real output, inflation, real exchange rates and international trade variables are dominated by domestic shocks. External shocks on average explain a fraction of no more than 10% of the variation in the endogenous variables considered. Moreover, real imports fail to display a cross-regional pattern, while technology shocks appear to be the disturbances playing a somewhat more important role in explaining consumer prices developments. Consumer prices and – depending on the disturbance considered – real imports are the variables showing larger impulse responses to unit shocks.
Keywords: C32; E32; F41; 330; business cycles; emerging markets; international trade; structural shocks; Konjunktur; Internationale Wirtschaft; Schock; Schwellenländer